Pengembangan Buku Pengayaan Teks Dialog Banyumasan Berbasis Pitutur Luhur Pupuh Gambuh untuk Siswa Kelas VIII SMP - Hayati, Meyla Nur; Nugroho, Yusro Edy; Purnomo, Sucipto Hadi (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
The objectives of this study are (1) to describe the needs of Javanese junior high school language students and teachers in Banyumas on the Banyumasan dialogue text enrichment book based on sublime pupuh Gambuh, (2) to make a prototype draft Banyumasan dialogue text enrichment book based on sublime pupuh Gambuh, and (3 ) describe the results of the prototype validation of Banyumasan dialogue text enrichment book based on sublime pupuh Gambuh. The method used in this study is the Research and Development (R & D) method. The development phase of the Banyumasan dialog text enrichment book based on the subline pupuh gambuh picture refers to the steps of Sugiyono (2010: 409) which are tailored to the research needs, namely: (1) potential and problems, (2) data collection, (3) product design, (4 ) product validation, and (5) product revisions. This study produced a Banyumasan dialog text enrichment book based on the advice of pupuh gambuh.